2002
DOI: 10.1161/01.atv.0000027101.40323.3a
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and E Intake Is Associated With Increased Paraoxonase Activity

Abstract: Objective-Paraoxonase (PON1), an esterase physically associated with high density lipoprotein, has been shown to inhibit atherogenic low density lipoprotein and high density lipoprotein oxidation. PON1 activity appears to be primarily under genetic control with some environmental modification and is a predictor of vascular disease. Vitamins C and E, dietary antioxidants, scavenge free-oxygen radical products that may depress PON1 activity. Therefore, we evaluated the relationship between dietary vitamin C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
106
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(119 citation statements)
references
References 68 publications
10
106
3
Order By: Relevance
“…This finding is in agreement with that previously described by Jarvik et al (2002) who reported the association of vitamin C and/or vitamin E intake with the antiatherogenic enzyme activity. The inhibition of LDL oxidation by HDL, which is due to the hydrolysis of lipid peroxidation, appears to be in part (Mackness, 1994) a function of the studied enzyme activities, which are components of HDL (Aviram et al, 2000a).…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in agreement with that previously described by Jarvik et al (2002) who reported the association of vitamin C and/or vitamin E intake with the antiatherogenic enzyme activity. The inhibition of LDL oxidation by HDL, which is due to the hydrolysis of lipid peroxidation, appears to be in part (Mackness, 1994) a function of the studied enzyme activities, which are components of HDL (Aviram et al, 2000a).…”
Section: Discussionsupporting
confidence: 94%
“…nase activity (30). Although the effects of carotenoids on atherosclerosis may be similar to those of vitamins C and E (i.e., a free radical species inhibition effect), lycopene may also have specific effects on cholesterol synthesis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changes in PON1 activity with the consumption of vegetables following ordinary meals may not occur in the postprandial state, as was in case of a study with blackcurrant juice, which is rich in water-soluble antioxidant polyphenols and ascorbic acid 26) . On the other hand, prior reports on human studies have shown that the intake of antioxidants exerts beneficial effects on PON1 activity [27][28][29][30][31] . Further research is required to determine the optimal quality and quantity of vegetables, duration of intervention, and health status of subjects.…”
Section: Discussionmentioning
confidence: 94%